Help or Harm? Criminalizing Intimate Partner Violence and Feminist Abolitionist Frames - Derr, Katelyn (Violence against women, 2025)
After decades of work by feminists to criminalize domestic violence, more recently feminist abolitionists have identified the harm that the carceral state has on all impacted by it, including victims/survivors. Based on interviews with a diverse sample of 22 women and men who were system impacted, we find evidence of cases in which the criminal legal system both helped and harmed the victim/survivor. We identify policy interventions that promote alternative methods to intervening in intimate partner violence relationships that center the victim/survivor, create safety, and reduce the increased surveillance and overall impact of the criminal legal system.